EVALUATION OF THE EFFECTIVENESS AND SUSTAINABILITY OF THE BUSINESS INCUBATOR PROGRAM IN CREATING ENTREPRENEURS IN INDONESIA - Citra Marcella Nazira; Lindawati Kartika (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The high unemployment rate is one of the factors that influence Indonesia in achieving decent work and economic growth. Creating entrepreneurs as solutions through entrepreneurship training programs has been organized by various parties. Bright Cube organized by IPB University is one of the business incubators that integrates all stakeholders. The purposes of this study are to analyze the implementation and sustainability strategy and evaluate the effectiveness of the 2nd batch of the Bright Cube program. The research methods used are descriptive analysis, Return on Training Investment, and SIPOC diagrams with a quantitative approach. Primary data were obtained through questionnaires and secondary data was obtained through a literature study. The results show that most participants are not satisfied with the resulting turnover. At the reaction level, participants tend to give a positive reaction to the program. At the learning level, there is an increase in knowledge and skills. At the behavioral level, participants are interested in becoming entrepreneurs. At the result level, participants recommend the program, and the ROTI result is positive. Several things need to be improved based on the evaluation. Therefore, this program has been running effectively and can be a successful example in order to achieving the entrepreneur national target